SERVER COMPUTER NETWORK BASED BUILDING NETWORK USING WI-FI (WIRELESS FIDELITY) ON WINDOWS SERVER 2003 OPERATING SISTEM - Muhammad Sugih Prakarsa; Fivtatianti Hendajani, SKom., MM (Jurnal Sistem Komputer, 2006)
Wireless Network or Wireless LAN is the networking technology that is not using thecable that can be found inside a computer network at the moment. These technologiesuse radio waves to make the interaction or communication between the computerunit. Wireless LAN is basically a radio device capable of connecting datacommunication between computers or a computer to a Local Area Network (LAN) orvice versa. The purpose of this paper is to use the wireless network can be built aLAN network without using cables that give the computer accessing the network.Access Point used as regulator of transmission between computers in a wirelessnetwork. Access Point acts like a HUB in a network that uses cables.